Mengukur Kepercayaan Dan Promosi Mahasiswa Terhadap Pembelian Melalui Aplikasi E-Commerce Di Universitas Labuhanbatu - Wardianto Wardianto; Abd. Halim; Yuniman Zebua (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to measure trust and student promotion towards purchases through the E-Commerce application at Labuhanbatu University. The research method used in this research is quantitative. The research sample uses incidental sampling technique is a sampling technique based on chance, that is, anyone who happens to meet the researcher can be used as a sample, if it is deemed that the person who happened to be met is suitable as a data source. This study uses non-probability sampling techniques because the population is unknown, and with purposive sampling as the sampling technique. Because the population of members is not known with certainty, the sample size is calculated using the Cochran formula with a research sample of 96 people. The data collection techniques used are observation, documentation studies and questionnaires. The method of analysis of this research is multiple linear regression with the SPSS program. The results of the study prove that Trust has a positive and significant effect on Purchases Through E-Commerce Applications on E-Commerce Applications at Labuhanbatu University. Promotion has a positive and significant effect on Purchases Through E-Commerce Applications on E-Commerce Applications at Labuhanbatu University. Trust and Promotion simultaneously have a positive and significant effect on Purchases Through E-Commerce Applications on E-Commerce Applications at Labuhanbatu University. The coefficient of determination of 0.330 means that Purchases Through E-Commerce Applications can be explained by the variables of Trust (X1) and Promotion (X2), amounting to 33%, while the remaining 67% can be explained by other variables not examined in this study. Keywords: Trust, Promotion, Purchasing Through E-Commerce Applications